Towards social justice: slowing down and attending to social justice through a community of philosophical inquiry - Jamieson, Victoria (Ethics and education, 2025)
Education is dominated by economic priorities and intellectual virtues that place emphasis on individual success, yet issues of social injustice are demanding of urgent attention. My hopes for social justice are rooted in education. I consider the place of schooling for continually reimagining social justice, and to think about what it might be to live with - and respond responsibly to one another. My arguments are grounded in dialogic pedagogies, specifically, the community of philosophical inquiry, as a space to question what social justice means, what it ought to mean, and how it could be otherwise. Resisting ideas that privilege certainty of knowledge of social justice, I consider the affordances of moving deeper into an unknowing rather than a settling of knowing. I turn to Nan Shepherd's The Living Mountain for a gentle force to render an attentiveness to thinking about what it is to know social justice.